Aging of 3D-printed maraging steel. (August 2019) - Thorsteinsdóttir, E G; Primdahl, D S; Zhang, Y B; Jensen, D Juul; Yu, T
Abstract: The effects of aging on the microstructural development and mechanical properties of a 3D-printed maraging steel have been investigated. The microstructures within printed, solution treated and aged samples are characterized by X-ray tomography and optical microscopy, as well as by scanning and transmission electron microscopy. The mechanical properties are estimated based on hardness measurements. The distribution of voids is found to be inhomogeneous, and even though the samples are 99.9% dense in the sample interior, the remaining voids affect significantly the hardness in the aged condition. In addition to precipitation, the aging treatment leads to formation of about 12% of reverted austenite. Together this leads to a strengthening of the material. Solution treatment results in homogenization of the microstructures such that after aging the solution treated samples are found to have higher strength than the samples that are just aged after printing. These results are discussed and compared to the aging behaviour of conventionally manufactured samples.